Prediction of Marital Burnout Based on Feelings of Loneliness and Emotional Divorce in Infertile Women - Mohammad Ghamari; Alireza Jafari; Samaneh Zareh Zardini (Gonabad University of Medical Sciences, 2021)
Background: Infertility is one of the most painful experiences of life leads to marital burnout. Psychological, emotional, and social factors affect marital burnout of infertile women. This study was done to predict marital burnout based on feelings of loneliness and emotional divorce in infertile women. Methods: The method of the research was descriptive-correlational. The participants were women (aged 25-45) referring to Ibn-e Sina Infertility Clinic in 2019 in Tehran. A sample of 175 participants was selected by convenience sampling and completed the Marital Burnout questionnaire, Feeling of Longlines questionnaire, and Emotional Divorce questionnaire. Data were analyzed by Pearson's correlation and multiple regression using SPSS v. 22. Results: The results indicated that there was a significant and positive relationship between loneliness and its subscales (lack of intimacy and lack of social network) (r= 0.62) and also a positive and significant relationship was found between emotional divorce and its subscales (feeling of separation from each other, feeling of loneliness the need for a companion, boredom, and restlessness) and marital burnout (r= 0.65). Also, feeling lonely and its subscales and emotional divorce and its subscales could predict the marital boredom of infertile women (P<0.01). Conclusion: Feeling lonely and emotional divorce have a significant and positive relationship with marital boredom and can predict marital boredom in infertile women.